Discharge after hip fracture surgery by mobilisation timing: secondary analysis of the UK National Hip Fracture Database - Katie Jane Sheehan; Aïcha Goubar; Orouba Almilaji; Finbarr C. Martin; C. W. Potter; Gareth Jones; Catherine Sackley; Salma Ayis (2020)
Abstract Objective To determine whether mobilisation timing was associated with the cumulative incidence of hospital discharge by 30 days after hip fracture surgery, accounting for potential confounders and the competing risk of in-hospital death. Method We examined data for 135,105 patients 60 years or older who underwent surgery for nonpathological first hip fracture between 1 January 2014 and 31 December 2016 in any hospital in England or Wales. We tested whether the cumulative incidences of discharge differed between those mobilised early (within 36 h of surgery) and those mobilised late, accounting for potential confounders and the competing risk of in-hospital death. Results A total of 106,722 (79%) of patients first mobilised early. The average rate of discharge was 39.2 (95% CI 38.9–39.5) per 1,000 patient days, varying from 43.1 (95% CI 42.8–43.5) among those who mobilised early to 27.0 (95% CI 26.6–27.5) among those who mobilised late, accounting for the competing risk of death. By 30-day postoperatively, the crude and adjusted odds ratios of discharge were 2.36 (95% CI 2.29–2.43) and 2.08 (95% CI 2.00–2.16), respectively, among those who first mobilised early compared with those who mobilised late, accounting for the competing risk of death. Conclusion Early mobilisation led to a 2-fold increase in the adjusted odds of discharge by 30-day postoperatively. We recommend inclusion of mobilisation within 36 h of surgery as a new UK Best Practice Tariff to help reduce delays to mobilisation currently experienced by one-fifth of patients surgically treated for hip fracture.